Investigation on the occurrence state and distribution behavior of elements in the separation and purification of crude silver by vacuum volatilization - Fractional condensation. (January 2023) - Wang, Shuangping; Xu, Baoqiang; Jiang, Wenlong; Kong, Lingxin; Kong, Xiangfeng; Yang, Bin; Xiong, Heng; Zhang, Teng; Qu, Chao; Zhang, Shanhui; Cui, Jiayou; Hou, Shaobin; et al.
Abstract: In this paper, an innovative idea of vacuum separation and purification of crude silver is proposed, and theoretical calculations and kilogram-scale experimental studies are carried out. The theoretical calculation results show that the order of saturated vapor pressure and theoretical maximum volatilization rate of each element in crude silver is Se > Te > Sb > Bi > Pb > Ag > Cu > Au. In the temperature range of 1373–1773 K, the separation coefficient and vapor-liquid equilibrium composition of Ag-Au and Ag-Cu alloys were calculated. The experimental results show that the crude silver is mainly composed of Ag-Au and Ag-Cu-Se-Te phases. Under the optimal experimental conditions, the total volatilization rate of crude silver after primary vacuum separation and purification was 90.36%, and the distribution rates of gold and silver in the residue were 98.26% and 1.10%, respectively. The secondary vacuum separation and purification of the first and second order condenser volatile from the primary vacuum separation and purification were carried out, and gold was enriched 149 and 128 times in the residue, respectively, and the main phases of the volatiles were Ag, Ag2 Se and Ag2 Te, of residue were Au-Sb phase, Au-Cu phase and Au-Ag-Cu phase. Highlights: An innovative, green and efficient vacuum separation and purification of crude silver was developed. A systematic theoretical study of the vacuum distillation was performed. Experiments on separation and purification of crude silver by vacuum volatilization-stage condensation were carried out. The occurrence state of each element in crude silver and experimental products were analyzed by EPMA. The behavior of the precious metal platinum and palladium were investigated.